Biological invasions and climate change amplify each other's effects on dryland degradation. (19th October 2021) - Ravi, Sujith; Law, Darin J.; Caplan, Joshua S.; Barron‐Gafford, Greg A.; Dontsova, Katerina M.; Espeleta, Javier F.; Villegas, Juan C.; Okin, Gregory S.; Breshears, David D.; Huxman, Travis E.
Abstract: Climate models predict that, in the coming decades, many arid regions will experience increasingly hot conditions and will be affected more frequently by drought. These regions are also experiencing rapid vegetation change, notably invasion by exotic grasses. Invasive grasses spread rapidly into native desert ecosystems due, in particular, to interannual variability in precipitation and periodic fires. The resultant destruction of non‐fire‐adapted native shrub and grass communities and of the inherent soil resource heterogeneity can yield invader‐dominated grasslands. Moreover, recurrent droughts are expected to cause widespread physiological stress and mortality of both invasive and native plants, as well as the loss of soil resources. However, the magnitude of these effects may differ between invasive and native grasses, especially under warmer conditions, rendering the trajectory of vegetated communities uncertain. Using the Biosphere 2 facility in the Sonoran Desert, we evaluated the viability of these hypothesized relationships by simulating combinations of drought and elevated temperature (+5°C) and assessing the ecophysiological and mortality responses of both a dominant invasive grass ( Pennisetum ciliare or buffelgrass) and a dominant native grass ( Heteropogan contortus or tanglehead). While both grasses survived protracted drought at ambient temperatures by inducing dormancy, drought under warmed conditions exceeded the tolerance limits of the native species, resulting in greater and more rapid mortality than exhibited by the invasive. Thus, two major drivers of global environmental change, biological invasion and climate change, can be expected to synergistically accelerate ecosystem degradation unless large‐scale interventions are enacted. Abstract : Written Summary: Under the warmer and drier conditions projected with climate change, greater physiological tolerances of invasive grasses are likely to enable their increased dominance. Invasive and native grasses were able to survive drought by triggering dormancy under ambient conditions, while the combination of drought and higher temperature exceeded the tolerance limits of the native species. This resulted in significant mortality of the native as compared to the invasive species. This study highlights the synergistic role biological invasions and climate change have on ecosystem degradation.